Informing About the Nocebo Effect Affects Patients’ Need for Information About Antidepressants—An Experimental Online Study - Nestoriuc, Yvonne; Pan, Yiqi; Kinitz, Timm; Weik, Ella; Shedden-Mora, Meike C. (Frontiers in Psychiatry, 2021)
Relevance. Understanding patients’ informational needs and adapting drug-related information are the prerequisites for a contextualized informed consent. Current information practices might rather harm by inducing nocebo effects. Objective. To investigate whether informing about the nocebo effect using a short information sheet affects patients’ need for information about antidepressants. Methods. A total of 97 patients taking recently prescribed antidepressants (≤ 4 months intake) were recruited over the internet and randomized to either receiving a one-page written information about the nocebo effect or a control text about the history of antidepressants. After experimental manipulation, informational needs about side effects and mechanisms of antidepressants were assessed with 3 and 7 items on categorical and 5-point Likert scales. Group differences in informational needs were calculated with Chi-square tests and ANOVAs. Results. Patients received antidepressants for depression (84.5%) or/and anxiety disorders (42.3%). Three participants (6.0%) of the nocebo group reported previous knowledge of the nocebo effect. After the experimental manipulation, participants in the nocebo group reported a reduced desire for receiving full side effect information, (Χ² (4, 97) = 12.714, Cramer’s V = .362, p = .013), and agreed more frequently to the usefulness of withholding information about possible side effects, (Χ² (4, 97) = 14.878, Cramer’s V = .392, p = .005). Furthermore, they desired more information about mechanisms of antidepressants, (F = 6.373, p = .013, partial η² = .063), and specifically, non-pharmacological mechanisms such as the role of positive expectations, (F = 16.857, p < .001, partial η² = .151). Conclusions. Learning about the nocebo effect can alter patients’ informational needs towards desiring less information about potential side effects of antidepressants and more information about general mechanisms such as expectations. Beneficial effects of including nocebo information into contextualized informed consent should be studied clinically concerning more functional information-seeking behavior, which may ultimately lead to improved treatment outcomes, such as better adherence and reduced side effect burden.